Philosophical Foundations concept of fundamentalization training of future specialists in information technology - Bardus, I. O. (Problems of Engineer-Pedagogical Education, 2018)
One of the challenges of training future professionals in the field of information technology in higher education is associated with low ability of students to quickly adapt to new conditions and self-mastery of new technologies. Fundamentalization of education based on universal general methodological knowledge and skills allows solving this problem. The article defines philosophical foundations of the concept of fundamentalization training future professionals in the field of information technology on the basis of the laws of dialectics and philosophical categories. The concept is based on three interrelated original positions: fundamentalization is a condition for effective training; physical and technical, mathematical and informational, philosophical and methodological subjects are fundamental training for IT professionals; system of differentiation and integration of fundamental and technical knowledge is a condition of productive occupation. The necessity of developing fundamentalized methodical system of training future IT professionals was approved based on the concept of system of differential-integrative fundamentalization of disciplines of computer direction.